The Presence of Turbulent and Ordered Local Structure within the ICME Shock-sheath and Its Contribution to Forbush Decrease - Zubair, Shaikh; Anil, Raghav; Bhaskar, Ankush (My University, 2017)
The transient interplanetary disturbances evoke short-time cosmic-ray flux decrease, which is known as Forbush decrease. The traditional model and understanding of Forbush decrease suggest that the sub-structure of an interplanetary counterpart of coronal mass ejection (ICME) independently contributes to cosmic-ray flux decrease. These sub-structures, shock-sheath, and magnetic cloud (MC) manifest as classical two-step Forbush decrease. The recent work by Raghav et al. has shown multi-step decreases and recoveries within the shock-sheath. However, this cannot be explained by the ideal shock-sheath barrier model. Furthermore, they suggested that local structures within the ICME’s sub-structure (MC and shock-sheath) could explain this deviation of the FD profile from the classical FD. Therefore, the present study attempts to investigate the cause of multi-step cosmic-ray flux decrease and respective recovery within the shock-sheath in detail. A 3D-hodogram method is utilized to obtain more details regarding the local structures within the shock-sheath. This method unambiguously suggests the formation of small-scale local structures within the ICME (shock-sheath and even in MC). Moreover, the method could differentiate the turbulent and ordered interplanetary magnetic field (IMF) regions within the sub-structures of ICME. The study explicitly suggests that the turbulent and ordered IMF regions within the shock-sheath do influence cosmic-ray variations differently.
Keywords: Sun; Coronal mass ejection (CME); Cosmic rays; Magnetic fields; Solar wind; ISM structure; Turbulence; CME